Spontaneous Regression of Pulmonary and Adrenal Metastases Following Percutaneous Radiofrequency Ablation of a Recurrent Renal Cell Carcinoma - Kim, Heejung; Park, Byung Kwan; Kim, Chan Kyo (Korean journal of radiology, 2008)
The spontaneous regression of metastatic lesions from renal cell carcinoma (RCC) is extremely rare, but may be encountered following cytoreductive treatments. We report a case of a recurrent RCC with multiple metastatic lesions which spontaneously regressed after undergoing radiofrequency ablation of the renal tumor.